2004
DOI: 10.1002/sres.653
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between performance in dynamic systems and intelligence

Abstract: System dynamics is a field that emphasizes the complex demands on human decisionmakers and the cognitive processes that are either wired into the brain by nature or by education or that are stimulated by nurture. The world can be regarded as a complex system and it is a fascinating question how the human brain has adapted to its complexity and survived. Of considerable interest are the human dispositions or characteristics that are responsible for survival and adaptation. Are individual differences in human ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 26 publications
7
88
2
Order By: Relevance
“…In the last 30 years, such microworlds have been used in numerous studies (for reviews, see Funke 1991Funke , 1995Funke and Frensch 2007;Osman 2009). There is a still ongoing debate if complex problem solving is a competence on its own (the related concept of operative intelligence is presented below), or if it is merely a subpart of ''intelligence'' Kluwe et al 1991;Kröner et al 2005;Rigas and Brehmer 1999;Strohschneider 1991;Süß 1996Süß , 1999Süß et al 1991;Wenke and Frensch 2003;Wittmann and Hattrup 2004). I will not answer this question here but point to one central question: Is complex problem solving a good case for complex cognition?…”
Section: Complex Cognitionmentioning
confidence: 96%
“…In the last 30 years, such microworlds have been used in numerous studies (for reviews, see Funke 1991Funke , 1995Funke and Frensch 2007;Osman 2009). There is a still ongoing debate if complex problem solving is a competence on its own (the related concept of operative intelligence is presented below), or if it is merely a subpart of ''intelligence'' Kluwe et al 1991;Kröner et al 2005;Rigas and Brehmer 1999;Strohschneider 1991;Süß 1996Süß , 1999Süß et al 1991;Wenke and Frensch 2003;Wittmann and Hattrup 2004). I will not answer this question here but point to one central question: Is complex problem solving a good case for complex cognition?…”
Section: Complex Cognitionmentioning
confidence: 96%
“…Earlier CPS-research in particular reported zero-correlations (e.g., Joslyn & Hunt, 1998;Putz-Osterloh, 1981), while more recent studies revealed moderate to high correlations between CPS and reasoning (e.g., Wittmann & Hattrup, 2004;Wittmann & Süß, 1999). For instance, Gonzalez, Thomas, and Vanyukov (2005) showed that performance in the CPSscenarios Water Purification Plant (0.333, p b 0.05) and Firechief (0.605; p b 0.05) were moderately to highly correlated with APM.…”
Section: Psychometrical Considerations For Measuring Cpsmentioning
confidence: 99%
“…First, an operator needs reasoning ability in order to develop hypotheses about the causal structure of the system. Second, reasoning with numbers has proven to be a predictor of performance in dealing with simulated complex systems (Wittmann andHattrup 2004, Kluge 2008). Third, an operator requires verbal and figural abilities in order to understand instructions, information and graphs given by the system (Wittmann andHattrup 2004, Kluge 2008).…”
Section: Cognitive Abilitymentioning
confidence: 99%
“…Second, reasoning with numbers has proven to be a predictor of performance in dealing with simulated complex systems (Wittmann andHattrup 2004, Kluge 2008). Third, an operator requires verbal and figural abilities in order to understand instructions, information and graphs given by the system (Wittmann andHattrup 2004, Kluge 2008). Drawing on the empirical results presented in the literature, it is hypothesised that cognitive ability is positively related to process control performance.…”
Section: Cognitive Abilitymentioning
confidence: 99%